Україна – втрачений шанс на перемогу Наполеона в 1812 році - Ковальчик, Рафал Віктор; Kovalczyk, Rafal Viktor (Східноєвропейський національний університет ім. Лесі Українки, 2014)
У статті проаналізовано причини невикористаних Наполеоном можливостей для перемоги над Росією у війні 1812 року. Автор доводить, що ключ перемоги французів знаходився в Украині, де були підготовлені необхідні матеріальні та людські ресурси для посилення військової могутності армії Наполеона. Однак, не зважаючи на дані розвідки і підготовлені штабами стратегічні плани, він був переконаний, що виграє війну з Росією в одній битві. Давши втягнути себе у безперспективне переслідування ворога, Наполеон зазнав поразки. The article describes the causes of the war in the year 1812 and the Ukrainian chance for victory over Russia. The work of intelligence services and headquarters of The Great Army and the army of The Duchy of Warsaw assumed that war will be divided in two years. Napoleon’s army were to be stopped on the border of former Poland. Basing on this land, especially Ukraine, the potential of the army should be increased and in the year 1813 Russia will be defeated. The weapons, horses and men were prepared in Ukraine. Despite it, as a result of Napoleon’s mistake, who believed in his lucky star and defeating Russia in one battle and march towards Moscow far from his army’s reserves, he lost this war. Russians took advantage of Napoleon’s mistakes as they knew that key to the victory was Ukraine, not Moscow.
Ukraine – lost chance for victory of Napoleon in 1812
Keywords: війна 1812 року; Російська імперія; Варшавське герцогство; Україна; Наполеон; Олександр І; war of 1812; Russian empire; Warsaw dukedom; Ukraine; Napoleon; Alexander I